Silicon telescope for prototype sensor characterization using particle beams and cosmic rays. (14th March 2017) - Abba, A.; Caponio, F.; Citterio, M.; Coelli, S.; Fu, J.; Lazzaroni, M.; Merli, A.; Monti, M.; Neri, N.; Petruzzo, M.; Rachevskaia, I.; Terzi, D.
Abstract: We present the design and the performance of a silicon strip telescope that we have built and recently used as reference tracking system for prototype sensor characterization. The telescope was operated on beam at the CERN Super Proton Synchrotron and also using cosmic rays in the laboratory. We will describe also the data acquisition system, based on a custom electronic board that we have developed, and the online monitoring system to control the quality of the data in real time.